2008
DOI: 10.1111/j.1600-079x.2008.00626.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of potential pro‐survival pathways regulated by melatonin in a murine senescence model

Abstract: We examined the effect of melatonin on pro-survival processes in three groups of mice. Untreated senescence-accelerated mice (SAMP8), melatonin-treated SAMP8 and untreated senescence-accelerated resistant mice (SAMR1) of 10 months old were studied. Melatonin (10 mg/kg) or vehicle (ethanol at 0.066%) was supplied in the drinking water from the end of the first month until the end of the ninth month of life. Differences in the Akt/Erk1-2 pathway and downstream targets were examined and no significant changes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
94
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 96 publications
(106 citation statements)
references
References 55 publications
(64 reference statements)
8
94
1
Order By: Relevance
“…Moreover, decreased SIRT1 expression has been found in patients with AD, and this decrease correlates with tau and Aβ levels (Julien et al 2009). Modulation of ADAM10 expression by SIRT1 has also been demonstrated (Gutierrez-Cuesta et al 2008;Donmez et al 2010). In our experimental paradigm, we found that resveratrol reduces the Aβ burden in treated SAMP8 brain concomitantly with increases in ADAM10 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, decreased SIRT1 expression has been found in patients with AD, and this decrease correlates with tau and Aβ levels (Julien et al 2009). Modulation of ADAM10 expression by SIRT1 has also been demonstrated (Gutierrez-Cuesta et al 2008;Donmez et al 2010). In our experimental paradigm, we found that resveratrol reduces the Aβ burden in treated SAMP8 brain concomitantly with increases in ADAM10 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, a decrease of SIRT1 expression with age in SAMP8 has been found [97] that correlate with a decrease in tau phosphorylation and with an increase in ADAM10 [58].…”
Section: Sirtuin 1 In Samp8: Biochemical Coincidences In Aging and Admentioning
confidence: 99%
“…SAMP8 shows spontaneous overproduction of soluble Aβ in the hippocampus [26] and cortex [58]. Evidence strongly suggests that an increase in soluble Aβ contributes to cognitive decline in aged SAMP8.…”
Section: Histopathological Similarities In Samp8 and Admentioning
confidence: 99%
See 1 more Smart Citation
“…Hardeland and colleagues [74] interpret this as evidence that mitochondrial biogenesis is stimulated by melatonin. Deacetylation of PGC-1a apparently depends on the SIrt1 protein, a protein that is upregulated by melatonin [75]; it is also upregulated by estradiol, apparently via the ubiquitin-proteasome system [76]. It is predicted that melatonin and the ubiquitin-proteasome system interact in regulating mitochondrial biogenesis and in inducing the expression of rOS-detoxifying enzymes.…”
Section: Melatonin/ubiquitin Interaction In Mitochondriamentioning
confidence: 99%